Next we look at the equation forlarger.
d^2 R
dρ^2
−
1
4
R= 0
This can be solved byR=e
−ρ
(^2) , so we explicitly include this.
R(ρ) =G(ρ)e
−ρ
2
We should also pick of thesmallrbehavior.
d^2 R
dρ^2
+
2
ρ
dR
dρ
−
ℓ(ℓ+ 1)
ρ^2
R= 0
AssumingR=ρs, we get
s(s−1)
R
ρ^2
+ 2s
R
ρ^2
−ℓ(ℓ+ 1)
R
ρ^2
= 0.
s^2 −s+ 2s=ℓ(ℓ+ 1)
s(s+ 1) =ℓ(ℓ+ 1)
So eithers=ℓors=−ℓ−1. The second is not well normalizable. WewriteGas a sum.
G(ρ) =ρℓ
∑∞
k=0
akρk=
∑∞
k=0
akρk+ℓ
The differential equation forG(ρ) is
d^2 G
dρ^2
−
(
1 −
2
ρ
)
dG
dρ
+
(
λ− 1
ρ
−
ℓ(ℓ+ 1)
ρ^2
)
G(ρ) = 0.
We plug the sum into the differential equation.
∑∞
k=0
ak
(
(k+ℓ)(k+ℓ−1)ρk+ℓ−^2 −(k+ℓ)ρk+ℓ−^1 + 2(k+ℓ)ρk+ℓ−^2
+(λ−1)ρk+ℓ−^1 −ℓ(ℓ+ 1)ρk+ℓ−^2
)
= 0
∑∞
k=0
ak((k+ℓ)(k+ℓ−1) + 2(k+ℓ)−ℓ(ℓ+ 1))ρk+ℓ−^2
=
∑∞
k=0
ak((k+ℓ)−(λ−1))ρk+ℓ−^1
Now weshift the sumso that each term containsρk+ℓ−^1.
∑∞
k=− 1
ak+1((k+ℓ+ 1)(k+ℓ) + 2(k+ℓ+ 1)−ℓ(ℓ+ 1))ρk+ℓ−^1 =
∑∞
k=0
ak((k+ℓ)−(λ−1))ρk+ℓ−^1